2021
DOI: 10.1111/tgis.12756
|View full text |Cite
|
Sign up to set email alerts
|

Modeling urban regions: Comparing random forest and support vector machines for cellular automata

Abstract: Cellular automat​on (CA) are important tools that provide insight into urbanization dynamics and possible future patterns. The calibration process is the core theme of these models. This study compares the performance of two common machine‐learning classifiers, random forest (RF), and support vector machines (SVM), to calibrate CA. It focuses on the sensitivity analysis of the sample size and the number of input variables for each classifier. We applied the models to the Wallonia region (Belgium) as a case stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Compared to the forest model (RF), ANN cannot extract diversified conversion rules accurately (Zhai et al., 2020). The RF model can efficiently mine the conversion rules of land‐use changes in different regions, which several previous studies have confirmed (Kamusoko & Gamba, 2015; Rienow et al., 2021; Yao et al., 2017; Zhang, Liu, et al., 2019). The DF algorithm is an ensemble of forests with characteristics of in‐model feature transformation, level‐by‐level processing, and sufficient adaptive model complexity (Zhou & Feng, 2019).…”
Section: Case Studysupporting
confidence: 52%
See 2 more Smart Citations
“…Compared to the forest model (RF), ANN cannot extract diversified conversion rules accurately (Zhai et al., 2020). The RF model can efficiently mine the conversion rules of land‐use changes in different regions, which several previous studies have confirmed (Kamusoko & Gamba, 2015; Rienow et al., 2021; Yao et al., 2017; Zhang, Liu, et al., 2019). The DF algorithm is an ensemble of forests with characteristics of in‐model feature transformation, level‐by‐level processing, and sufficient adaptive model complexity (Zhou & Feng, 2019).…”
Section: Case Studysupporting
confidence: 52%
“…The natural environmental conditions, such as elevation and slope, which restrict the use of land parcels, were chosen as driving factors of urban land change (Rienow, Mustafa, Krelaus, & Lindner, 2021). The geometry attributes of land parcels may influence urban land‐use change were also considered in urban land‐use change, including the area, perimeter, and shape of land parcels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In applying the different LULC change prediction models, ref [50] utilized hybrid LR-MC-CA and obtained an accuracy of 89% between simulated and actual land use for case study of Tehran. For urban growth modeling, ref [51] employed RF-CA and SVM-CA models which exhibited a high certainty for modeling complex urban growth in the Wallonia region (Belgium). For forecasting LULC change in Attica (Greece), ref [52] applied RF-CA with notably high overall accuracy of 88.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Integration of machine learning models and cellular automata (CA) is a typical approach to simulate urban growth (Rienow & Goetzke, 2015; Rienow, Mustafa, Krelaus, & Fragkias, 2021; Shafizadeh‐Moghadam, 2019). Over the past three decades, simulating LULC changes using CA has gained increasing popularity among scholars (Gounaridis, Chorianopoulos, Symeonakis, & Koukoulas, 2019; Mirbagheri & Alimohammadi, 2018; Munshi, Zuidgeest, Brussel, & Van Maarseveen, 2014; Rienow & Goetzke, 2015).…”
Section: Introductionmentioning
confidence: 99%